REGIONAL EMPLOYMENT PLANNING GRAND DESIGN: A CASE STUDY IN KARANGANYAR - Siti Aisyah Rahayu; Kusnandar Kusnandar; Diana Tantri Cahyaningsih (Universitas Islam Indonesia, 2013)
AbstractThe aims of this research are to design employment planning with a proper method, to get a prediction of supply and demand of labor, and to create a planning program in employment development in Karanganyar region to increase quality of employment and productivity as well as to raise employment welfare. It finds that Karanganyar region has an industrial and agricultural typology and that industrial sector has a greater regional gross domestic product (RGDP) than province RGDP on average. It also finds that service sector has employment elasticity greater than that of the other sectors and that the agriculture sector experiences aa decrease on employment demand.Keywords: Population, unemployment, employment planningJEL classification numbers: J21, J22, J23AbstrakTujuan dari penelitian ini adalah untuk merancang perencanaan kerja dengan metode yang tepat, mendapatkan prediksi permintaan dan penawaran tenaga kerja, dan juga membuat perencanaan program pembangunan ketenagakerjaan di daerah Karanganyar untuk meningkatkan kualitas pekerjaan dan produktivitas serta meningkatkan kesejahteraan tenaga kerja. Studi ini menemukan bahwa wilayah Karanganyar memiliki tipologi industri dan pertanian, dan bahwa sektor industri memiliki produk domestik regional bruto (PDRB) yang lebih besar dari PDRB rata-rata provinsi. Studi ini juga menemukan bahwa sektor jasa memiliki elastisitas lapangan kerja lebih besar dari sektor lain dan bahwa permintaan pekerjaan di sektor sektor pertanian mengalami penurunan.Kata kunci: Penduduk, pengangguran, perencanaan kerjaJEL classification numbers: J21, J22, J23